Residential greenspace and anxiety symptoms among Australian women living in major cities: A longitudinal analysis - Tafzila A. Mouly; Gita D. Mishra; Perry Hystad; Mark Nieuwenhuijsen; Luke D. Knibbs (Environment International, 2023)
Despite an increasing number of studies demonstrating the potential mental health benefits of greenspace, few longitudinal studies have been reported. We aimed to assess associations between two metrics of residential greenspace exposure and anxiety symptoms in a cohort of Australian women living in major cities.Our study comprised 3,938 women, born between 1973 and 78. Anxiety symptoms in the previous month were assessed at follow-up every three years during 2003–2018, using the anxiety subscale of the Goldberg Anxiety and Depression Scale. The three-month seasonal average normalized difference vegetation index (NDVI) was estimated from 30 m Landsat satellite images in a 500 m buffer (NDVI500m) around participants’ address at each survey (higher NDVI indicates more green vegetation). The annual fractional cover of non-photosynthesising vegetation was estimated (fNPV500m, with higher values indicating greater levels of dead leaf litter or dry grass).A generalised estimating equation assessed associations between greenspace measures and anxiety symptoms (as odds ratios [ORs]), adjusting for repeated outcomes and individual-level covariates. Additional analyses focused on women experiencing substantial changes in between-survey exposure due to moving, and adjusting for nitrogen dioxide (NO2) and fine particulate matter (PM2.5) exposure, among others.A standard deviation (SD) (0.12 units) increase in NDVI500m was significantly associated with lower odds of anxiety symptoms (OR: 0.96, 95% CI: 0.93–0.99) in the adjusted model. An SD (5.2%) increase in annual fNPV500m was consistent with the direction expected for that exposure, but not significant in the adjusted model (OR: 1.03, 95% CI: 0.99–1.07). NDVI500m was modestly attenuated when air pollutants were adjusted for, while fNPV500m only became significant when PM2.5 was adjusted for. Between-survey contrasts had no clear effect for NDVI500m. Moving to a higher fNPV500m area, compared with a similar fNPV500m area, was consistently associated with anxiety symptoms (OR: 1.15, 95% CI: 1.02–1.31). NDVI500m was generally associated with lower odds of anxiety symptoms, while fNPV500m was generally associated with higher odds of anxiety, depending on the covariates considered.